IMPLEMENTASI MODEL PEMBELAJARAN BARAMEAN UNTUK MENINGKATKAN KOLABORASI DAN HASIL BELAJAR MATEMATIKA - Alvi Rahman; Ari Hidayat; Akhmad Riandy Agusta; Dessy Dwitalia Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low collaboration skills and mathematics learning outcomes of fifth-grade students at SDN Kelayan Timur 12 Banjarmasin. The study aims to describe teacher activities, analyze student activities, collaboration skills, and mathematics learning outcomes through the implementation of the BARAMEAN learning model, which combines Problem-Based Learning, Make a Match, and Game-Based Learning. The study employed Classroom Action Research (CAR) consisting of two cycles, each with two meetings. The subjects were 27 fifth-grade students (14 male and 13 female) in the 2024/2025 academic year. Data were collected through observation, tests, and documentation, then analyzed descriptively. The findings showed significant improvements in every observed aspect. Teacher activities increased from a score of 27 (good) in the first meeting to 36 (very good) in the fourth meeting. Student activities improved from 44% (quite active) in the first meeting to 93% (very active) in the fourth meeting. Collaboration skills rose from 56% (quite skilled) to 93% (very skilled). Meanwhile, student learning outcomes increased from 37% mastery in the first meeting to 93% in the fourth meeting, exceeding the classical completeness criteria. These results indicate that implementing the BARAMEAN model fosters active participation, enhances collaboration, and significantly improves mathematics learning outcomes. Thus, the BARAMEAN model can be an innovative and effective alternative for mathematics learning in elementary schools.